Testing considerations for phosphatidylinositol‐3‐kinase catalytic subunit alpha as an emerging biomarker in advanced breast cancer. (22nd July 2020) - Toppmeyer, Deborah L.; Press, Michael F.
Abstract: Breast cancer is the most common cancer in women, and approximately 71% of carcinomas are hormone receptor‐positive (HR+) and human epidermal growth factor receptor 2‐not‐amplified (HER2‐negative). Pathogenesis of breast cancer is associated with dysregulation of several signaling pathways, including the phosphatidylinositol‐3‐kinase (PI3K) pathway. PIK3CA, the gene encoding PI3K catalytic subunit p110α, is mutated in 20%‐40% of breast cancer patients. Several PI3K inhibitors have been developed and one, alpelisib, was recently approved for use in PIK3CA ‐mutated, HR+, HER2‐negative advanced breast cancer. There are numerous types of assays and methods used in clinical studies to determine PIK3CA status in cancers. Additionally, there are several factors to consider for PIK3CA testing in clinical practice, including choice of assay, source of sample, and test timing. In this review, we discuss the use of PIK3CA as a biomarker to guide treatment decisions in patients with HR+, HER2‐negative advanced breast cancer, as well as practical considerations and recommendations for testing. Abstract : PIK3CA may be used as a biomarker to guide treatment decisions in patients with HR+, HER2‐negative ABC. PIK3CA mutation may be assessed through either tissue or liquid biopsy using PCR‐ or NGS‐based assays.